Effect of a 12-Week Concurrent Training Intervention on Cardiometabolic Health in Obese Men: A Pilot Study - Amaro-Gahete, Francisco J.; Ponce-González, Jesús G.; Corral-Pérez, Juan; Velázquez-Díaz, Daniel; Lavie, Carl J.; Jiménez-Pavón, David (Frontiers in Physiology, 2021)
The present study aimed to investigate the effects of a 12-week concurrent training intervention on cardiometabolic health in obese men. Twelve obese men (42.5±5.3 years old) participated in the current 12‐weeks randomized controlled trial with a parallel group design. The participants were randomly assigned to a concurrent training group or to a no-exercise control group. Anthropometry and body composition assessment were determined by electrical bio-impedance. Blood samples were obtained and a cardiometabolic risk Z-Score as calculated. Energy metabolism related parameters (i.e. resting metabolic rate, respiratory quotient and substrate oxidation in both resting conditions and during exercise) were determined by indirect calorimetry. Echocardiographic studies were performed using an ultrasound system equipped with a transducer to measure cardiac function. A significant decrease of weight (= - 4.21 kg; i.e. primary outcome), body mass index (= - 1.32 kg/m2), fat mass (= - 3.27 kg), blood pressure (= - 10.81 mmHg) and cardiometabolic risk Z-Score (= - 0.39) was observed in the exercise group compared with the control group (all P<0.05), while no significant changes were noted in waist circumference, lean mass, bone mineral content, glycaemic and lipid profiles, liver function, nor in energy metabolism related parameters (all P>0.1). Moreover, a significant increment of left ventricular end diastolic diameter (= - 4.35 mm) was observed in the exercise group compared with the control group (P=0.02). A 12-week concurrent training intervention is an effective strategy to induce weight and fat loss with simultaneous reductions of blood pressure and cardiometabolic risk, and improving cardiac function in obese men .